1988
DOI: 10.1111/j.1476-5381.1988.tb16567.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for dopaminergic co‐transmission in dog mesenteric arterial vessels

Abstract: 1 The overflow of dopamine and noradrenaline (NA) from the main trunk of the dog mesenteric artery and its proximal branches during prolonged depolarization (120min) by K+ (52imM) was quantified by high performance liquid chromatography with electrochemical detection. 2 K+-induced depolarization resulted in release of both dopamine and NA. The amount of NA released from both blood vessels declined progressively throughout the experiment. In the main trunk the same pattern of release was observed for dopamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The role of dopamine in the sympathetic nervous system is not limited only to providing a means for the synthesis of the neurotransmitter noradrenaline; 64 the amine can also act as a cotransmitter in some circumstances. 65 Non-neuronal cells capable of producing dopamine are distributed in the kidney and intestine. 66 These renal tubular and intestinal epithelial cells are endowed with a high capacity to synthesize dopamine from its immediate precursor, L-DOPA, where the amine plays a pivotal role as a local hormone with autocrine and paracrine function, regulating water and electrolyte homeostasis.…”
Section: Therapeutic Applications Of Comt Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of dopamine in the sympathetic nervous system is not limited only to providing a means for the synthesis of the neurotransmitter noradrenaline; 64 the amine can also act as a cotransmitter in some circumstances. 65 Non-neuronal cells capable of producing dopamine are distributed in the kidney and intestine. 66 These renal tubular and intestinal epithelial cells are endowed with a high capacity to synthesize dopamine from its immediate precursor, L-DOPA, where the amine plays a pivotal role as a local hormone with autocrine and paracrine function, regulating water and electrolyte homeostasis.…”
Section: Therapeutic Applications Of Comt Inhibitorsmentioning
confidence: 99%
“…In the peripheral nervous system, dopamine is the first catecholamine in the biosynthesis of neurotransmitters such as norepinephrine and epinephrine. The role of dopamine in the sympathetic nervous system is not limited only to providing a means for the synthesis of the neurotransmitter noradrenaline; the amine can also act as a cotransmitter in some circumstances . Non-neuronal cells capable of producing dopamine are distributed in the kidney and intestine .…”
Section: Therapeutic Applications Of Comt Inhibitorsmentioning
confidence: 99%
“…The basis behind NOMI's pathophysiology shows that by preserving blood supply to viscera, perfusion in mesenteric vessels is compromised; thus, in theory, a drug that can vasodilate these vessels can play a crucial role in providing sufficient perfusion to distressed vessels 2 . Prominent animal studies have shown that Fenoldopam acts as a vasodilator and increases blood flow in mesenteric arteries [3][4] .…”
Section: To the Editormentioning
confidence: 99%